The Syrian Football Coaches Planned Thinking Level According to their Fulfilled Achievements - بحبوح, فؤاد; خدوج, ميسم (Latakia University Journal -Medical Sciences Series, 2021)
When the sports coach practicing the training profession, it's important for him to work to strengthen the various creative capacities that ensure him quick understanding of different playing situations during competition, and recall his previous experiences that he has been through, where these experiences would help to find the appropriate solutions rapidly and picture what the opponent intends to do in order to achieve the objects sought by the sports coach. May the prior experiences and the positive feedback resulted from achieving the coaches champions and successes have the greatest effect on these coaches' raised planned thinking level, so the close knowing of planned thinking level of the football coaches according to their achieved successes is the main objective of this research using descriptive method through survey and analyzing sample of (32) football coaches, of whom (12) coaches have their own sports achievements, (20) with no achievements at all, the research use planned thinking scale in addition to meetings with some Asian football lecturers. The study found that planned thinking level is high with coaches who have achieved champions and sports achievements, and they were also distinguished from the rest by their high education, focus attention, good match management and self-confidence.